2022
DOI: 10.1371/journal.pone.0261172
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses associated with attentional engagement and disengagement from threat in high socially anxious children: Evidence from temporal-spatial PCA

Abstract: Background Cognitive models indicated that social anxiety disorder (SAD) would be caused and maintained by a biased attentional processing of threatening information. This study investigates whether socially anxious children may present impaired attentional engagement and disengagement from negative emotional faces, as well as their underlying event-related potential responses. Methods and findings Fifteen children with high levels of social anxiety (HSA; 9 boys; mean age = 9.99y; SD = 1.14) and twenty low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 105 publications
2
4
0
Order By: Relevance
“…In line with our hypothesis, we found associations between increased anxiety and depression and attenuated P3 amplitudes, indicative of suboptimal evaluation of environmental inconsistency or conflict (e.g., a NoGo trial; Bruin et al., 2001). Our findings are consistent with P3 amplitude reduction reported in people with diagnosed depression (Houston et al., 2003; Klawohn et al., 2020; Nan et al., 2018; Santopetro et al., 2022, 2020) and anxiety (Bechor et al., 2019; Éismont et al., 2009; Wauthia et al., 2022; Xu et al., 2014) compared to unaffected comparators. Atypical ACC activation is characteristic of people with internalizing disorders (Blair et al., 2012; Lichenstein et al., 2016; Shang et al., 2014).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with our hypothesis, we found associations between increased anxiety and depression and attenuated P3 amplitudes, indicative of suboptimal evaluation of environmental inconsistency or conflict (e.g., a NoGo trial; Bruin et al., 2001). Our findings are consistent with P3 amplitude reduction reported in people with diagnosed depression (Houston et al., 2003; Klawohn et al., 2020; Nan et al., 2018; Santopetro et al., 2022, 2020) and anxiety (Bechor et al., 2019; Éismont et al., 2009; Wauthia et al., 2022; Xu et al., 2014) compared to unaffected comparators. Atypical ACC activation is characteristic of people with internalizing disorders (Blair et al., 2012; Lichenstein et al., 2016; Shang et al., 2014).…”
Section: Discussionsupporting
confidence: 90%
“…NoGo trial; Bruin et al, 2001). Our findings are consistent with P3 amplitude reduction reported in people with diagnosed depression (Houston et al, 2003;Klawohn et al, 2020;Nan et al, 2018;Santopetro et al, 2022Santopetro et al, , 2020 and anxiety (Bechor et al, 2019;Éismont et al, 2009;Wauthia et al, 2022;Xu et al, 2014) compared to unaffected comparators. Atypical ACC activation is characteristic of people with internalizing disorders (Blair et al, 2012;Lichenstein et al, 2016;Shang et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The latter findings reflect a heightened tendency for threatening stimuli to captivate selective attention 9 . An electroencephalogram study conducted on children (aged between 8 to 12 years old) showed that those with high levels of social phobia exhibited increased N2 amplitudes in response to the presentation of disgusted faces compared to their healthy counterparts 76 . This finding is noteworthy given that this neurophysiological pattern is typical of difficulties in attentional disengagement from the threat 76 .…”
Section: Discussionmentioning
confidence: 99%
“…An electroencephalogram study conducted on children (aged between 8 to 12 years old) showed that those with high levels of social phobia exhibited increased N2 amplitudes in response to the presentation of disgusted faces compared to their healthy counterparts 76 . This finding is noteworthy given that this neurophysiological pattern is typical of difficulties in attentional disengagement from the threat 76 . Interestingly, no behavioral differences (reaction times) were detected between groups in this study 76 .…”
Section: Discussionmentioning
confidence: 99%